2018
DOI: 10.1007/s00404-018-4733-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between genital mycoplasmas infection and human papillomavirus infection, abnormal cervical cytopathology, and cervical cancer: a systematic review and meta-analysis

Abstract: We found that U. urealyticum and M. genitalium may increase the risk of high-risk HPV infection, while U. urealyticum, U. parvum, and M. hominis may increase the risk of abnormal cervical cytopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 41 publications
7
40
2
4
Order By: Relevance
“…Among them, the Ureaplasma parvum and their related taxa manifested higher richness in the baseline HPV-positive group compared with the baseline HPVnegative group. This is consistent with previous studies in different populations of the world indicating that Ureaplasma parvum was associated with a significantly increased risk of overall HPV infection and increased risk of abnormal cervical cytopathology (20)(21)(22). It was reported that the infection of Ureaplasma could lead to scarring and damage of the epithelium (23), suggesting that infection of the reproductive tract with Ureaplasma parvum might also increase the risk of HPV infection by facilitating viral infections.…”
Section: Discussionsupporting
confidence: 92%
“…Among them, the Ureaplasma parvum and their related taxa manifested higher richness in the baseline HPV-positive group compared with the baseline HPVnegative group. This is consistent with previous studies in different populations of the world indicating that Ureaplasma parvum was associated with a significantly increased risk of overall HPV infection and increased risk of abnormal cervical cytopathology (20)(21)(22). It was reported that the infection of Ureaplasma could lead to scarring and damage of the epithelium (23), suggesting that infection of the reproductive tract with Ureaplasma parvum might also increase the risk of HPV infection by facilitating viral infections.…”
Section: Discussionsupporting
confidence: 92%
“…Induction of HPV in this way is particularly interesting based on the association between Mycoplasma and cervical lesions. Infection with M. genitalium increases the rate of infection with an HPV genotype associated with a high-risk of developing cervical cancer [35]. Recent work has shown that mycoplasma also increases the risk of development of cervical lesions, supporting the association we report in this study [35].…”
Section: Discussionsupporting
confidence: 90%
“…Infection with M. genitalium increases the rate of infection with an HPV genotype associated with a high-risk of developing cervical cancer [35]. Recent work has shown that mycoplasma also increases the risk of development of cervical lesions, supporting the association we report in this study [35]. Mycoplasma can establish persistent, intracellular infections in epithelia cells, which may lead to bacterial vaginosis and/or cervicitis.…”
Section: Discussionsupporting
confidence: 88%
“…Роль ХЦ как ко-фактора при раке шейки матки доволь-но существенна. Исcледователи отметили положительную связь между воспалением шейки матки и плоскоклеточными интраэпителиальными поражениями [17,18].…”
Section: впч-инфекция цервицит и рак шейки маткиunclassified